Brahma darshan : life in space divine - Dave, Harshadarāya Tribhuvanadāsa, 1913- (Bochasanwasi Shri Aksharpurushottam Sanstha, 1970)
On the life and teachings of Swami Sahajananda, 1781-1830, founder of the Svāmī Nārāyaṇa sect of Vaishnavism.